Digital Government Stage Evaluation in Population and Civil Registry Office (Disdukcapil) of Kutai Kartanegara Regency - Cathas Teguh Prakoso (Jurnal Borneo Administrator, 2022)
Recent developments show scholars argue that when electronic government systems reach certain stages, they will develop into Digital Government. However, studies on Digital Government evaluation, especially in the Indonesian context, are still few. With that in mind, this article aims to describe the maturity of the digital government system in the Population and Civil Registry Office (Disdukcapil) of the Kutai Kartanegara Regency. It is based on the assumption that Disdukcapil has successfully implemented electronic government, as proven by their multiple recognitions and can be considered at the digital government stage. Field observation and in-depth interviews with key informants are employed to collect the relevant data. All the data are then analyzed qualitatively, and then it uses digital government evolution variables developed by Janowski (2015) to determine the stage of Disdukcapil digital government. The result shows that within a four-stage maturity level, the digital government of Disdukcapil of Kutai Kartanegara Regency has reached the third stage, based on the fulfilment of each stage's variables. It is hoped that this study can contribute to Digital Government studies in Indonesia